EFEKTIVITAS PEMBELAJARAN DARING DENGAN MEDIA ONLINE BERBASIS GOOGLE CLASSROOM PADA POKOK BAHASAN GELOMBANG TERHADAP HASIL BELAJAR SISWA SMA N 2 TONDANO - Gela Lompad; Ferdy Dungus; Alfrits Komansilan (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
Learning is the most important activity in the entire educational process in school. The outbreak of the Corona Virus Disease 2019 (Covid-19) pandemic has had a major impact on all existing areas; teaching and learning processes are also carried out at home online or online via Google in the education sector. This study aims to determine the effectiveness of online learning with Google-based online media classroom waves on the physical learning outcomes of SMA Negeri 2 Tondano students This research method is an experimental method. The research data are based on the post-test results. The average physics learning outcomes of the experimental class students was 82 with a maximum score of 90 and a minimum score of 70. While the average physics learning outcomes for the control class students was 62 with a maximum score of 80 and a minimum score of 50, normality test of the data showed that the experimental class data and the control class are normally distributed, then the hypothesis is tested. Data on student learning outcomes from the post-test. The results of the investigation by calculating the t-test formula show that the H_O hypothesis is rejected. From this it can be concluded that the average learning outcomes of the experimental physics class are higher than those of the control classes.